Understanding Barriers and Behavioural Determinants of Financial Inclusion: Evidence from Empirical Investigation - Hardev Singh,Gagandeep Kaur,Dr. Kaveri Khound; Taruna,Manpreet Kaur,Amanpreet Kaur, (European Economic Letters (EEL), 2025)
Financial inclusion is vital for inclusive economic development in India; yet, behavioural, structural, and digital barriers persist, particularly in Haryana, where significant rural–urban disparities remain. This study examines the barriers, drivers, and behavioural determinants of financial inclusion using primary data from 380 households across 12 districts, selected through a multistage sampling process. The structured questionnaire assessed financial literacy, trust, digital readiness, perceived usefulness, perceived risk, attitudes toward digital finance, and social influence. Data were analyzed using Exploratory Factor Analysis, Confirmatory Factor Analysis, and Partial Least Squares Structural Equation Modelling. Findings show that financial literacy, trust, digital readiness, and perceived usefulness significantly enhance inclusion behaviour, whereas perceived risk, documentation challenges, and low digital capability impede participation. Rural households face notably higher behavioural and structural constraints than urban households. The model explains 62.4% of the variance in inclusion behaviour, highlighting the central role of behavioural factors and suggesting targeted policy interventions for Haryana.